Pendidikan Islam dan Lingkungan Hidup - Hidayat, Ara (Jurnal Pendidikan Islam, 2015)
This article discusses about relations of Islam with environmental education, fiqhul bi’ahand Islamic education based on environmentally. The shifting paradigm in elements oflife especially in education is believed to be a necessity to consider the development ofthe sophistication of environment and as a strategic-ideological effort to increase thecapacity of understanding which in turn could construct a new awareness to supportsbalancing of the ecosystem. Alternative models of education that we could develop is“madrasah adiwiyata”—madrasah of care and environment cultured—aims to increasethe capacities, knowledge, and understanding of management and protection ofenvironment in sustainable development through education. Madrasah adiwiyata isthe right and ideal, to realize responsibility for the protection and management of theenvironment. Madrasah / school is a place to obtains all the sciences and norms, aswell as ethical human beings who can be the basis for the creation of welfare towardssustainable development.